2018
DOI: 10.18632/aging.101574
|View full text |Cite
|
Sign up to set email alerts
|

A joint analysis of metabolomic profiles associated with muscle mass and strength in Caucasian women

Abstract: Both loss of muscle mass and strength are important sarcopenia-related traits. In this study, we investigated both specific and shared serum metabolites associated with these two traits in 136 Caucasian women using a liquid chromatography-mass spectrometry method. A joint analysis of multivariate traits was used to examine the associations of individual metabolites with muscle mass measured by the body mass index-adjusted appendicular lean mass (ALM/BMI) and muscle strength measured by hand grip strength (HGS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Of interest, a lot of circulating metabolites that are different in RA patients compared to controls could be related to associated metabolic syndrome, since choline metabolism (especially TMAO and carnitine), aminoacids (alanine, glutamine, glutamate, arginine, aspartate, asparagine, histidine, methionine, cysteine, lysine, branched-chain amino acids (BCAA), phenylaniline, tyrosine, and tryptophan) and phospholipids (phosphatydilcholines) also change in those with metabolic syndrome [80]. Several works on muscle mass have also suggested that some circulating metabolites can be biomarkers of muscle mass and sarcopenia [81]. Even though both fat tissue and muscle, as well as associated immune cells in these inflamed tissues, can be sources of metabolites, it is unknown how much they can contribute to the pool of circulating metabolites.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Of interest, a lot of circulating metabolites that are different in RA patients compared to controls could be related to associated metabolic syndrome, since choline metabolism (especially TMAO and carnitine), aminoacids (alanine, glutamine, glutamate, arginine, aspartate, asparagine, histidine, methionine, cysteine, lysine, branched-chain amino acids (BCAA), phenylaniline, tyrosine, and tryptophan) and phospholipids (phosphatydilcholines) also change in those with metabolic syndrome [80]. Several works on muscle mass have also suggested that some circulating metabolites can be biomarkers of muscle mass and sarcopenia [81]. Even though both fat tissue and muscle, as well as associated immune cells in these inflamed tissues, can be sources of metabolites, it is unknown how much they can contribute to the pool of circulating metabolites.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…A total of 119 unrelated Caucasian females, aged 20-40 years, were recruited through Louisiana Osteoporosis Study (LOS) (Du et al, 2017, Zhao et al, 2018, a repertoire of more than 16,000 subjects (by the end of August 2019) collected for genomic, transcriptomic, methylomic, metabolomic, and metagenomic studies of complex diseases/traits, particularly for osteoporosis. All the subjects were living in New Orleans, Louisiana and its surrounding areas and were self-identified as being of European origin.…”
Section: Subjectsmentioning
confidence: 99%
“…The LC-MS based metabolomics platform developed by Dr. Garrett's lab in the Southeast Center for Integrated Metabolomics at University of Florida was used to perform the metabolomic analysis. The detailed experimental procedures have been previously described (Liu et al, 2017, Zhao et al, 2018.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Previous research has identified metabolites associated with gait speed [9][10][11][12], other gait parameters [10], grip strength [11], combined muscle mass and strength outcomes [13,14], and Short Physical Performance Battery (SPPB) score [11]. Although these findings are promising, limitations of past work include the sole use of cross sectional examination without longitudinal follow up [10,11,[13][14][15][16], sole use of targeted metabolomics approaches which are restricted to pathways of presumed biological relevance [10][11][12][14][15][16], small numbers of metabolites tested [10][11][12][13][14][15][16], small sample sizes [13][14][15][16], and lack of adjustment for multiple comparisons [10,11,14,16]. Thus, there is a compelling need for research on the relationship between serum metabolites and physical performance that takes advantage of longitudinal data and utilizes agnostic metabolomic methods.…”
Section: Introductionmentioning
confidence: 99%